2019
DOI: 10.1093/infdis/jiz660
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of the Immune Status of Humans Infected With Zoonotic Gorilla Simian Foamy Viruses

Abstract: Background Zoonotic simian foamy viruses (SFVs) establish persistent infections in humans, for whom the long-term consequences for health are poorly described. In this study, we aimed to characterize blood-cell phenotypes and plasma biomarkers associated with gorilla SFV infection in humans. Methods We used a case-control design to compare 15 Cameroonian hunters infected with gorilla SFV (cases) to 15 controls matched for age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Nevertheless, our results suggest that foamy viruses may be able to quickly acquire enhanced fitness through acquisition of a different env gene through recombination, which would, in the case studied here, result in increased cell-cell fusion and at the same time release of higher absolute infectivity and higher per-particle infectivity. Given the known very high propensity to template switching of foamy viruses [ 54 ], the possibility of such recombination events should be kept in mind in light of the well-known zoonotic potential [ 9 , 10 , 11 , 12 , 13 , 52 ]. Frequent exchange of the variant parts of env has been proposed as one possible explanation for the high evolutionary stability of the foamy virus genome and its diversity in the env gene [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our results suggest that foamy viruses may be able to quickly acquire enhanced fitness through acquisition of a different env gene through recombination, which would, in the case studied here, result in increased cell-cell fusion and at the same time release of higher absolute infectivity and higher per-particle infectivity. Given the known very high propensity to template switching of foamy viruses [ 54 ], the possibility of such recombination events should be kept in mind in light of the well-known zoonotic potential [ 9 , 10 , 11 , 12 , 13 , 52 ]. Frequent exchange of the variant parts of env has been proposed as one possible explanation for the high evolutionary stability of the foamy virus genome and its diversity in the env gene [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous foamy viruses are present in coelacanth [ 5 ], amphibia [ 6 ], fish [ 7 ], birds and serpentines [ 8 ]. SFVs have demonstrated a potential for zoonotic infection in Africa [ 9 , 10 , 11 ] and also in Asia [ 12 , 13 ]. Recently, zoonotic infections with gorilla SFV were found to be associated with hematological abnormalities and altered biochemical markers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This area of research is particularly interesting because FV infections are apparently apathogenic in the hosts, but in vitro, FV infection triggers cytopathic effects and ultimately leads to cell death [22]. However, recent case-control studies among Cameroonian hunters infected with gorilla SFV identified an association of T-cell differentiation, monocyte activation, and hematological abnormalities with SFV infection [112,113]. These and a similar study that characterized an association of FFV with chronic kidney disease in cats [114] suggest that more research is needed to explore in vivo pathological changes by FVs.…”
Section: Innate Immune Sensing Of Foamy Virusesmentioning
confidence: 99%
“…Humans can be infected by monkey bites and scratches and develop fetal encephalitis with a mortality exceeding 70% in the absence of treatment and 20% even with adequate treatment [ 13 ]. SFV is ubiquitous in several primate species and usually causes persistent infection [ 14 , 15 ], whereas SFV infections in humans are well documented to cause subclinical hematologic changes [ 16 , 17 , 18 ]. In addition, Adenovirus and Rotavirus are important zoonotic pathogens that might lead to high rates of mortality in humans and animals [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%